Production of gamma-polyglutamic acid with tunable molecular weight via electrofermentation using soybean protein concentrate as a feedstock - Sunday O. Oguntomi; Yongjia Zhang; Obinna M. Ajunwa; Cinzia Calvio; Sze Shin Low; Simone Morra; Wenhua Yu; Haibo Zhou; Jian Hao; Enrico Marsili (Bioresource Technology, 2026)

Correction: [FeFe] hydrogenases with modified azadithiolate bridgeheads serve as unidirectional hydrogen oxidation catalysts - Manon T. Lachmann; James A. Birrell; Simone Morra; Patricia Rodríguez-Maciá (JBIC Journal of Biological Inorganic Chemistry, 2026)

[FeFe] hydrogenases with modified azadithiolate bridgeheads serve as unidirectional hydrogen oxidation catalysts - Manon T. Lachmann; James A. Birrell; Simone Morra; Patricia Rodríguez-Maciá (JBIC Journal of Biological Inorganic Chemistry, 2026)
Semi-synthetic [FeFe] hydrogenases hold exciting potential as tuneable artificial metalloenzymes for efficient hydrogen conversion (H 2 $$\rightleftharpoons$$ 2 H + + 2e − ). This work investigates the role of the bridgehead ligand in the [FeFe] hydrogenase active site through the study of two bridgehead-modified active-site variants (2-oxapropane 1,3-dithiolate, ODT, and propane 1,3-dithiolate, PDT). Replacing the native 2-azapropane 1,3-dithiolate (ADT) bridgehead with ODT or PDT significantly modifies the active site’s electronic structure and disrupts proton-transfer; yet, some catalytic activity remains, suggesting that alternative catalytic pathways may exist. Notably, when adsorbed onto an electrode, the ODT enzymes operate as proficient catalysts for hydrogen oxidation at higher oxidative overpotentials, achieving current densities of up to 1 mA cm − 2 , comparable to those observed for the respective ADT enzyme under the same conditions. Electrochemical analysis reveals similar catalytic behaviour between the ODT and PDT enzymes, suggesting that a proton transfer pathway between the active site and the protein environment still operates, albeit disrupted, in both bridgehead variants under these conditions. Insights into the electronic and catalytic interplay of these modifications could advance the optimisation of semi-synthetic [FeFe] hydrogenases and design of new bioinspired catalysts. Graphical abstract

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Richer, greener, and more thermophilous? – a first overview of global warming induced changes in the Italian alpine plant communities within the new GLORIA ITALIA NETWORK - Francesco Porro; Simone Orsenigo; Thomas Abeli; Andrea Mondoni; Anna Corli; Fiona J. White; Silvano Lodetti; Marcello Tomaselli; Alessandro Petraglia; Michele Carbognani; Matteo Gualmini; T’ai G. W. Forte; et al. (Plant Biosystems, 2022)

[FeFe]-hydrogenases as biocatalysts in bio-hydrogen production - Simone Morra; Francesca Valetti; Gianfranco Gilardi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)